2007
DOI: 10.1213/01.ane.0000266447.23037.e4
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil Halves the EC50 of Propofol for Successful Insertion of the Laryngeal Mask Airway and Laryngeal Tube in Pediatric Patients

Abstract: Remifentanil 7.5 ng/mL reduced the propofol concentration required for airway insertion by half, and improved conditions for insertion. Propofol concentrations for insertion of the LMA and LT were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Propofol has a greater depressant effect on jaw tone, laryngeal and pharyngeal reflex than thiopentone [11,12]. Similarly, remifentanil suppresses jaw tone and airway reflex, and its combination with propofol for induction has been shown to provide adequate conditions for laryngoscopy and intubation without the need for concomitant muscle relaxants [13]. Apneic and analgesic effects of remifentanil may help to improve intubating conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has a greater depressant effect on jaw tone, laryngeal and pharyngeal reflex than thiopentone [11,12]. Similarly, remifentanil suppresses jaw tone and airway reflex, and its combination with propofol for induction has been shown to provide adequate conditions for laryngoscopy and intubation without the need for concomitant muscle relaxants [13]. Apneic and analgesic effects of remifentanil may help to improve intubating conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the ED50 of propofol was 2.99 µg/ml (95% CI 2.85-3.12 µg/ml) for smooth laryngeal mask placement when the anesthetic contained 1.5 µg/kg fentanyl (Yu et al, 2006). Clinical trials have shown that propofol alone (2.5-3 mg/kg) cannot meet the throat mask airway placement conditions; therefore, anesthesia is often combined with opioids (Park et al, 2007). Anesthesia induction with propofol alone requires higher doses with consequent fluctuations in hemodynamics and respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…In children, Min et al [15] showed that the optimal bolus dose of remifentanil for successful tracheal intubation was 0.56 μg/kg in 50% of children during inhalation induction using 5% sevoflurane in oxygen without neuromuscular blocking agents. Park et al [16] found that the coadministration of remifentanil halved propofol requirements and improved insertion conditions for LMAs and laryngeal tubes in children. Jeon et al [9] showed that a remifentanil effect-site concentration of 2.0 ng/mL administered before a propofol effect-site concentration of 6 μg/mL created excellent conditions for insertion of the CobraPLA on the first attempt with minimal hemodynamic disturbances.…”
Section: Discussionmentioning
confidence: 99%